2001
DOI: 10.1089/105072501316973163
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Struma Ovarii: An Unusual Presentation

Abstract: Malignant struma ovarii is a rare disease; only a few cases are well documented in the literature. Thus, the overall prognosis and modalities of treatment are still somewhat controversial. In this article, the authors report a case of malignant struma ovarii discovered 4 years after ovariectomy after metastasis to the lungs and bones. Review of the pathology of the ovarian struma did not reveal the classic criteria of malignancy, there were, however, many features considered to be atypical and thus suspicious.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 13 publications
(16 reference statements)
0
35
0
Order By: Relevance
“…Malignant struma ovarii is a very rare disease [9][10][11][12]. The clinical course of extraovarian spread and the gold standard therapy have not been fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant struma ovarii is a very rare disease [9][10][11][12]. The clinical course of extraovarian spread and the gold standard therapy have not been fully established.…”
Section: Discussionmentioning
confidence: 99%
“…Checrallah et al [7] described a case of malignant struma ovarii that metastasized to the lungs and pelvic bones. McGill et al [6] presented a case of metastatic struma ovarii to the right upper extremity, mediastinum, and bilateral hips.…”
Section: Discussionmentioning
confidence: 99%
“…Wynne et al [8] reported a case of metastatic struma ovarii to the ischium. Of the bone metastasis previously reported in the English literature, the specific bone locations varied; 4 cases occurred in the spine [4,9,10,11], 2 in skull [12,13], 4 in pelvic bone [6,7,8,10], and one case did not provide the exact location of the bone metastasis [14]. It is interesting that both of our patients had metastases to the left pelvic bone, and this report together with those in the literature makes pelvic bone the most favored site for bony metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations